Prevalence of Acute Compartment Syndrome of Limbs: A Retrospective Study (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Acute compartment syndrome (ACS) is a serious and well known complication of limb trauma. This condition is an orthopaedic emergency and is associated with significant morbidity if not diagnosed promptly and treated effectively.Materials and Methods: This is a retrospective cross sectional study on the scope of compartment syndrome among patients with limbs traumas those were treated between April 2015 and November 2018 in a United Nations level-II Hospital at Kaga-Bandoro in Central African Republic leaded by Bangladesh Medical Contingent. The medical records as well as data from the orthopaedic registrars of patients with limb injuries were studied. Limb injuries considered for in-hospital treatments with or without other associated system injuries were included while patients with any form of arterial diseases or claudication were excluded.Results: A total of 320 patients met the inclusion criteria among them only 2.81% had ACS and male young adults were mostly affected. Commonest underlying pathology was tibia fracture 44.4%, followed by due to tight traditional bone setters’ splints 22.2% and 11.1% patients from burns eschar.Conclusion: ACS of limb is not very common. Early clinical diagnosis in the absence of pressure monitoring equipment and emergency fasciotomies are recommended to salvage the limbs.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 200-203